Determinants of tax morale: Empirical study on micro, small and medium enterprises in Java - Rama Daneshwara; Riko Riandoko (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2023)
One of the reasons Indonesia's tax ratio has yet to reach its target is the informal sector and tax avoidance. The individual's desire to pay or avoid taxes is related to tax morals. This study aims to determine the effect of trust in the government, trust in tax administration, national pride, the likelihood of being caught in tax evasion efforts, and the level of punishment on tax morale. The research object is the owner of the micro, small, and medium enterprises (MSMEs) in Java. The research approach used is quantitative research. The data used are primary data consisting of 395 respondents' answers collected. Data analysis used the Ordinary Least Squares (OLS) method. The test results state that trust in the government, trust in tax administration, national pride, likelihood of being caught in tax evasion efforts, and the level of punishment simultaneously and partially have a significant positive effect on tax morale.